Novel WISP3 mutations causing progressive pseudorheumatoid dysplasia in two Chinese families - Yan, Wenjin (Hum Genome Var, 2016)
Progressive pseudorheumatoid dysplasia (PPD) is a rare disease caused by mutations in the gene for Wnt1-inducible signaling pathway protein 3 (WISP3). Here, we report the clinical and radiographic manifestations of two Chinese PPD patients. We performed whole-exome sequencing for one patient and sequenced the WISP3 for the other. Three WISP3 mutations (c.396T>G, c.721T>G and c.679dup) were identified; the two missense mutations were novel. Our study expanded the WISP3 mutation spectrum.